IN VITRO FREE RADICAL SCAVENGING ACTIVITY AND PHENOL AND FLAVONOID CONTENT OF NERIUM INDICUM, PELTOPHORAM PTEROCARPUM AND ROSA SPPS. FLOWER EXTRACTS - H, PADALIA; P, Moteriya; R, Satasiya; S, CHANDA (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: The aim of the present study was to evaluate antioxidant activity and phenol and flavonoid content of three flowers viz. Nerium indicum, Peltophoram pterocarpum and Rosa spps extracts. Methods: The extraction was done by individual cold percolation method using solvents like hexane, ethyl acetate and acetone. Total phenolic and total flavonoid content of different extracts was determined using Folin-ciocalteu assays and aluminium chloride colorimetric method respectively. Antioxidant activity was carried out by ferric reducing antioxidant power (FRAP) and ABTS radical cation scavenging activity. Results: Total phenol content was more in acetone extract while total flavonoid content was more in ethyl acetate extract, in all the three flower species. FRAP activity was maximum in acetone extracts while ABTS activity was more in ethyl acetate extracts. Conclusion: Phenolic and non-phenolic compounds contribute to the antioxidant activity of these three flower extracts. The best antioxidant activity was shown by P. pterocarpum flowers suggesting it to be a good source of natural antioxidants. Keywords: Flowers, Antioxidant activity, 2, 2'-Azino-bis-(3-ethyl) benzothiazoline-6-sulfonic acid, Ferric reducing antioxidant power, Total phenol content, Total flavonoid content.